Bullying participant roles and gender as predictors of bystander intervention. Issue 3 (11th November 2016) - Jenkins, Lyndsay N.; Nickerson, Amanda B.
Abstract : Although the importance of peer bystanders in bullying has been recognized, there are few studies that examine the phenomenon in relation to Latané and Darley's (1970) classic Bystander Intervention Model, which states that there are five stages of bystander intervention: (i) notice the event; (ii) interpret the event as an emergency that requires assistance; (iii) accept responsibility for intervening; (iv) know how to intervene or provide help; and (v) implement intervention decisions. This study examined preliminary evidence of reliability and validity of the Bystander Intervention Model in Bullying (Nickerson, Aloe, Livingston, & Feeley, 2014), and the extent to which bullying role behavior (bullying, assisting, victimization, defending, and outsider behavior) and gender predicted each step of the model with a sample of 299 middle school students. Results of a Confirmatory Factor Analysis supported a five‐factor structure of the measure corresponding to the steps of the model. There was evidence of convergent validity and Cronbach alpha for each subscale exceeded .75. In addition, students who reported defending their peers were more likely to also engage in all five steps of the bystander intervention model, while victims were more likely to notice events, and outsiders were less likely to intervene. Gender differences and gender interactions were also found. Aggr. Behav. 43:281–290, 2017. © 2016 Wiley Periodicals, Inc.